The relationship between HbA1c levels and erythrocyte sedimentation rate in type 2 diabetes mellitus patients based on hypertension status - Hotmaria Simanullang; Tiarnida Nababan; Refi Ikhtiari (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Measuring random or fasting blood glucose levels does not fully reflect the quality of long-term blood glucose control. Therefore, more accurate monitoring of glycemic status in patients with diabetes mellitus is performed through the HbA1c test. This test is used as an indicator of successful diabetes mellitus control and to minimize the risk of cardiovascular complications and improve patients' quality of life. Purpose: To determine the relationship between HbA1c levels and erythrocyte sedimentation rate (ESR) values ​​in type 2 Diabetes Mellitus patients based on hypertension status at the Bunda Thamrin Medical Laboratory, Medan. Method: A quantitative approach was employed with a descriptive correlational analytical design. The population was 70 patients with type 2 diabetes mellitus, with a sample size of 70 obtained through a specific sampling method. Data on HbA1c levels and ESR values ​​were analyzed to determine their relationship to the patients' hypertension status. Results: No significant differences in HbA1c levels (p=0.746) or ESR values ​​(p=0.259) were found between the hypertensive and normotensive patient groups. However, a clinically significant trend was found in ESR values, with the hypertensive group having a higher proportion of normal ESR values ​​(p=0.066). Conclusion: No significant differences were found between HbA1c levels and ESR values ​​based on hypertension status. Nevertheless, HbA1c has the potential to be an indirect predictor of inflammatory status. Optimal glycemic control remains crucial to reduce the risk of cardiovascular complications through anti-inflammatory mechanisms, especially in patients with hypertension who require more comprehensive management.